Determinants of Inflation in Indonesia: The Role of Monetary Variables, External Debt, and the Rupiah Exchange Rate (2001–2025) - Rosyana Ayu Kusuma; Eni Setyowati (Vifada Management and Digital Business, 2026)
The relationships between money supply growth, the depreciation of the Indonesian rupiah, and inflation have remained inconsistent over time, while previous empirical studies have reported mixed findings regarding the determinants of inflation. This study examines the effects of money supply growth, real interest rates, external debt growth, and the rupiah exchange rate on inflation in Indonesia and identifies the most influential determinant. Annual time-series data covering the period 2001–2025 (25 observations) were collected from Statistics Indonesia, Bank Indonesia, the Ministry of Finance, and the World Bank. The analysis employs the Autoregressive Distributed Lag–Error Correction Model (ARDL–ECM) with the bounds testing approach to estimate both short-run and long-run relationships. The results confirm the existence of a long-run equilibrium relationship among the variables, as indicated by an F-Bounds statistic of 15.85255. The error correction term (ECT = −0.982171, p < 0.01) demonstrates a rapid adjustment toward long-run equilibrium following short-run deviations, while the model explains 86.60% of the variation in inflation (Adjusted R² = 0.8660). In the long run, real interest rates and the exchange rate significantly influence inflation, whereas in the short run only the exchange rate remains statistically significant. In contrast, money supply growth and external debt growth do not exert significant effects in either the short or long run. These findings contribute to the inflation literature by jointly examining monetary and external-sector determinants within a unified ARDL–ECM framework using the most recent Indonesian data and by distinguishing their short-run and long-run impacts. The study highlights the critical role of exchange rate stability in maintaining price stability and underscores the importance of coordinated monetary and exchange rate policies in controlling inflation.